Peranan Peraturan Kebijakan Dalam Pelaksanaan Fungsi Pemerintahan - Luh Ketut Ayu Manik Sastrini; Ni Made Witari Dewi (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Policy regulations are free policy products determined by state administration officials in the context of carrying out government tasks. The policies set by the government in the form of policy regulations are not based on orders from the law or not based on authority based on the law. The policies of state administration officials are then outlined in a certain format so that they can be applied generally or apply equally to every citizen. The format of policy regulations is simpler than the format of statutory regulations. Policy regulations are enforced and obeyed like other legal regulations. Policy regulations are formal forms of policy determined by state administrative officials based on the principle of discretion. In the practice of government administration, policy regulations and statutory regulations coexist. Policy regulations are not statutory regulation. Policy maker does not have the authority to form laws and regulations. Policy regulations generally provide instructions regarding how a government agency will act in carrying out government authority that is not bound to any person. The formation of policy regulations by state administration officials expressed in formats such as announcements, guidelines or circulars are not based on legislative authority, but based on government authority.